REFORMASI BIROKRASI PERIZINAN BERUSAHA MELALUI ONLINE SINGLE SUBMISSION (OSS) - Pujiono Pujiono; Dewi Sulistianingsih; Laga Sugiarto (Arena Hukum, 2022)
This paper aims to analyze the implementation of the Online Single Submission (OSS) with its advantages and disadvantages, as well as the obstacles in operating it. This study uses the socio legal method, where the legal aspect is related to the implementing OSS as a form of licensing transformation in the investment sector reduces investment processes and procedures in Indonesia, which have been considered convoluted, high-cost and do not guarantee legal certainty or the many institutions that have the authority to issue permits. Whereas the social aspect analyzes the advantages of the OSS system in displaying real time data from time to time related to business actor data, investor data that can be used as a basis for making a decision. The results shows that the constraints in the implementation of OSS are unstable internet networks in some parts of Indonesia and not all available human resources who operate the OSS system in the regions, which results in various policies made by local governments that contradict the OSS system.